DOVER BEACH: SEMIOTICS IN THEORY AND PRACTICE - Subur Laksmono Wardoyo (TEFLIN, 2005)
Decoding the dramatic situation, intertextuality, and connotation of a poetic text can be very helpful for its interpretation. How the theory of those three aspects of semiotics might be applied in Dover Beach is to be the focus of this article.